SonarQube in action - Campbell, G. Ann (Manning Pub., 2014)
SonarQube in Action teaches you how to effectively use SonarQube following the continuous inspection model. This practical book systematically explores SonarQube's core Seven Axes of Quality (design, duplications, comments, unit tests, complexity, potential bugs, and coding rules). With well-chosen examples, it helps you learn to use SonarQube's review functionality and IDE integration to implement continuous inspection best practices in your own quality management process.